Food waste, circular economy, and policy with oligopolistic retailers. (25th June 2023) - Correani, Luca; Morganti, Patrizio; Silvestri, Cecilia; Ruggieri, Alessandro
Abstract: The food chain is intrinsically linked to agriculture and enables a transition towards a Circular Economy (CE) system and a resource efficient future. Accordingly, the development of analytical models appears particularly useful to address these challenges and to assess CE strategies. In this study, we develop a theoretical model to investigate the relationship between market structure and food waste. We consider an oligopolistic market with N differentiated firms (retailers), where each firm sells a final perishable good (food) in a context of strategic interaction. We use this model to analyse and compare two policy instruments aimed to reduce food waste, namely taxation and circular economy approach. The social welfare index, given by the sum of firms' profits and consumers' utility (surplus), is used to make this comparison. Food waste is an endogenous consequence of the interaction between competing retailers and consumers; interestingly, theoretical results suggest that the individual retailer's food waste is positively correlated with market concentration and the quality of goods. In general, circular economy shows a higher welfare than taxation especially when customers are particularly sensitive to the amount of goods available on the shelves. The study is completed by numerical simulations. Graphical abstract: Image 1 Highlights: Oligopoly model developed to analyse two policy instruments aimed to reduce FW. Social welfare index is used to make this comparison. FW is positively correlated with market concentration and the quality of goods. CE shows a higher welfare than taxation.